SOCIAL COMMUNICATION IN BUILDING RELIGIOUS SPIRITUALITY: Study of Flaming South Lampung - Fitri Yanti; Eni Amaliah (AL-TAHRIR, 2018)
Abstrak: This study discusses the Post-Conflict of South Lampung, seeing that the more frequent and easy our people explode with anger without being accompanied by ratios and common sense, so that anger is resolved in an anarchist manner in the form of murder, destruction and even massacre. Moral destructive events and even the dimensions of ethnicity, religion and culture should not be repeated again, it is feared that the Indonesian people will become a sick society that does not prioritize peace and mutual interests and the sick community because this country is increasingly populated by citizens with bad images that are not civilized society. The author uses a qualitative design of sampling. This paper presents alternatives in building a process of post-conflict social communication to build tolerance, inclusiveness and respect for plurality and communicative dialogue between people by creating harmonious relations between religious communities with approaches to strengthening noble values that are packaged with local government policies by giving authority to legal apparatus for violations that occur and facilitate cultural and community leaders in the context of the conflict space peace agreement to the lower community so that the community can maintain and maintain plurality by being able to live side by side.الملخص: بحثت هذه الدراسة في الوضع بعد الصراع في لامبونج الجنوبية، نظرا إلى سهولة وسرعة نشوء غضب المجتمع وتكرّر وقوعه دون أن يشاركه تفكير سليم صحيح منهم، حتى أدى هذا الغضب إلى اتخاذ أسلوب العنف – في التغلب عليه – كالقتل والتدمير بل وقتل الناس. والمفروض أن لا تقع هذه الوقائع المفسدة للأخلاق ثانية، بل ويدخل فيها بعد القبيلة، والدين والثقافة . وخِيف أن يكون المجتمع الأندونيسي مجتمعا مريضا لا يهتم بالأمن والسلامة والشؤون الجماعية، ويكون مريضا لكثرة المواطنين المتّسمين بسيمة سيّئة (مجتمع غير مدني). استخدم الباحث في هذا البحث المنهج الكيفي وأخذ العيّنة. حاولت هذه الدراسة عرض الاختيارات في بناء التواصل الإجتماعي بعد النزاع وهي بثّ روح التسامح، والانفتاح، والاعتبار  بوجود التعددية  واستمرارية بناء التواصل بين الأمم أو المجتمعات على أساس التراحم فيما بينهم بمدخل تقوية القيم الكريمة في ضوء قرارات الحكومة المحلية بإعطاء السلطة لرجال القضاء على جميع أشكال انتهاك القانون  وتوظيف رجال الثقافة والمجتمع في سياق اتفاق السلام حتى المجتمع عامة كي يحافظوا على التعدّدية ويعيشوا آمنين فيما بينهم.Abstrakt: Kajian ini membahas tentang Pasca Konflik Lampung Selatan, melihat semakin sering dan mudahnya masyarakat kita meledak amarahnya tanpa diiringi dengan rasio dan akal sehat, sehingga amarah tersebut diselesaikan dengan cara anarkis yang berupa pembunuhan, perusakan bahkan pembantaian. Seharusnya kejadian-kejadian yang merusak moral bahkan membawa dimensi suku, agama dan budaya ini tidak terulang kembali justru dikhawatirkan masyarakat Indonesia menjadi masyarakat sakit yang tidak mengedepankan kedamaian dan kepentingan bersama serta masyarakat sakit karena negeri ini semakin banyak dihuni oleh warga dengan citra buruk yang tidak civilized society. Penulis menggunakan rancangan kualitatif pengambilan sampel. Tulisan ini memaparkan alternatif dalam membangun proses komunikasi social pasca konflik membangun sikap toleran, inklusif dan menghargai pluralitas serta komunikatif melakukan dialog antar umat yaitu dengan menciptakan keharmonisan hubungan antar umat beragama dengan pendekatan penguatan nilai-nilai luhur yang dikemas dengan kebijakan pemerintah setempat dengan memberikan kewenangan kepada para aparat hukum atas pelanggaran yang terjadi dan memfasilitasi tokoh-tokoh budaya dan masyarakat pada konteks ruang konflik kesepakatan damai hingga masyarakat bawah sehingga masyarakat dapat menjaga dan merawat kemajemukan dengan bisa hidup berdampingan.